Confronting marginalisation in education : a framework for promoting inclusion - Messiou, Kyriaki (Abingdon, Oxon : Routledge, 2012)
'One of the key challenges facing schools today is that of reducing marginalisation amongst pupils in educational contexts. With a particular focus on primary school classrooms, Confronting Marginalisation in Education provides guidance and illustrative examples of the ways in which teachers can include all of their learners in the academic and social experiences they provide. This book offers a detailed focus on how the voices of learners can be used to reveal those children most likely to experience some kind of marginalisation and, in addition, to highlight issues that are related to the inclusion of all. These frequent vocal accounts are contextualised within an analytical framework that places particular emphasis on the importance of listening to children. In order to understand and, more importantly, address marginalisation through the views of children, Messiou therefore develops the text around a usable framework that consists of a unique four-step process: Step 1: Opening doors: Enabling voices to emerge Step 2: Looking closely: Bringing concerns to the surface Step 3: Making sense of the evidence: Sharing data with learners Step 4: Dealing with marginalisation: Encouraging inclusive thinking and practice. This framework shows how the systematic collecting of evidence can ease the process of understanding, help tackle marginalisation, and promote inclusion in a way that can be incorporated into the daily work of practitioners. Importantly, the book focuses on all learners, including those that might experience marginalisation but whose voices might have not previously been heard'--
Includes bibliographical references (p. [135]-142) and index.
Keywords: Children with social disabilities -- Education; Children with social disabilities -- Education (Primary).; Inclusive education; Marginality, Social